The crisis of connection roots, consequences, and solutions - Way, Niobe 1963-; Ali, Alisha 1970-; Gilligan, Carol 1936-; Noguera, Pedro; Kirkland, David E. (New York University Press, 2018)
"The Crisis of Connection: Roots, Consequences, and Solutions" makes a compelling argument that one of the main problems of the 21st century is the crisis of connection both between and within individuals. The book provides evidence of the crisis and explores its causes and consequences. Eventually, "The Crisis of Connection" suggests possible solutions to the state of disconnection that the world has found itself in, encouraging the readers to pursue common humanity" --Provided by publisher.